2019
DOI: 10.3390/su11010240
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation by Motivation in Ecotourism: Application to Protected Areas in Guayas, Ecuador

Abstract: Among tourists, there is recently a growing interest in the environment and enjoying the natural world. This study analyzed the motivations and segmentation of the demand for ecotourism, using functional theory as a reference point. Empirical analysis was carried out in Santay National Recreation Area, Morro Mangrove Wildlife Refuge, and Samanes National Recreation Area. The sample included 382 surveys, obtained in situ using the simple random sampling method. Factorial analysis and non-hierarchical segmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 76 publications
3
31
0
2
Order By: Relevance
“…These findings are similar to those of (Lee et al, 2014), who found seven motivational dimensions in ecotourism (self-development, interpersonal relationships, rewards, development of personal relationships, escape, ego-defensive function, and appreciation of nature as the primary motivations. In addition, the findings above support other previous research related to the dimensions which motivate ecotourists (McGehee & Kim, 2004;Weaver & Lawton, 2002;Zeppel, 2008;Carvache-Franco et al, 2019b).…”
Section: Discussionsupporting
confidence: 88%
“…These findings are similar to those of (Lee et al, 2014), who found seven motivational dimensions in ecotourism (self-development, interpersonal relationships, rewards, development of personal relationships, escape, ego-defensive function, and appreciation of nature as the primary motivations. In addition, the findings above support other previous research related to the dimensions which motivate ecotourists (McGehee & Kim, 2004;Weaver & Lawton, 2002;Zeppel, 2008;Carvache-Franco et al, 2019b).…”
Section: Discussionsupporting
confidence: 88%
“…While much of the previous ecotourism literature has assumed that tourist choose ecotourism as a result of their inherent environmental and social values, Blamey and Braithwaite (1997) acknowledge that tourists' environmental values may not be the only reason for gravitating towards an ecotourism experience. Several motivations for ecotourism have been identified including self-development, building relationships, escape, relaxation, and the nature experience itself (Adam et al, 2019;Carvache-Franco et al, 2019). Many of these motivations form segments of visitors.…”
Section: Value-belief-norm Theorymentioning
confidence: 99%
“…First is the potential for omitted variable bias. While our goal was a parsimonious comparison of the influence on environmental values and symbolic conspicuous consumption on intention to engage in ecotourism, our model did not include other motivations related to ecotourism intention such as socialization, adventure, and the nature experience itself (Adam et al, 2019;Beh & Bruyere, 2007;Carvache-Franco et al, 2019, Smith et al, 2014 or the relationship between the VBN constructs and Social Return. It is suggested that future research add these motivations to the model as well as the influence of personal norms and environmental values on social return to see which variables remain significant predictor of ecotourism and how the VBN constructs influence social return.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Two papers look at ecotourism, the most common product associated with sustainable tourism development. Carvache-Franco et al [34] develop a segmentation model for ecotourists visiting Ecuador. Based on a survey of 382 tourists analysed using factorial analyses and non-hierarchical segmentation, they present findings that will help public institutions and private companies improve their tourism offerings and develop more efficient marketing plans, when seeking to develop an ecotourism offering in a destination.…”
Section: Overview Of Articles In the Special Issuementioning
confidence: 99%